THE EFFECT OF OIL PALM EMPTY FRUIT BUNCHES (EFB) COMPOST AND N, P, K FERTILIZERS ON THE GROWTH AND YIELD OF LOWLAND RICE (Oryza sativa L.) - Ardian, Ardian; Hariani, D. Z.; Pramana, A.; Idwar, Idwar (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The use of chemical fertilizers can cause environmental problems. A compost of oil palm empty fruit bunches (OPEFB) is one alternative to reducing chemical fertilizers used for rice (Oryza sativa L.). This research to determine the effect and obtain the best dose of OPEFB compost and N, P, K fertilizers in lowland rice Batang Piaman Variety was conducted in Padang Mutung Village, Kampar, for six months using a factorial completely randomized design (CRD). The first factor was three levels of OPEFB (0 t.ha-1, five t.ha-1, ten t.ha-1), and the second factor was four levels of fertilizer N, P and K (0-0-0 kg.ha-1, 125-75-25 kg.ha-1, 150-100-50 kg.ha-1, and  175-125-75 kg.ha-1 of Urea-TSP-KCl). The ANOVA results showed that the combination of various doses of EFB compost and N, P, and K fertilizers did not significantly affect plant height, the number of tillers, the number of productive tillers, heading days, the weight of 1,000 grains, and the harvest index. The combination of giving EFB compost at a dose of 10 t.ha-1 and Urea fertilizer 175 kg.ha-1 TSP 125 kg.ha-1increased the percentage of pithy grain to 93.91%, and the weight of dry milled grain is 2,023.3 g.4m-2.